Thoracic duct drainage patterns in heterotaxy - Daniel A. Castellanos; Emily M. Bucholz; Katherine Bai; Jesse J. Esch; David Hoganson; Stephen P. Sanders; Raja Shaikh; Sunil J. Ghelani; David N. Schidlow (Journal of Cardiovascular Magnetic Resonance)
Background: Disordered lymphatic drainage is common in congenital heart diseases (CHD), but thoracic duct (TD) drainage patterns in heterotaxy have not been described in detail. This study sought to describe terminal TD sidedness in heterotaxy and its associations with other anatomic variables. Methods: This was a retrospective, single-center study of patients with heterotaxy who underwent cardiovascular magnetic resonance imaging at a single center between July 1, 2019 and May 15, 2023. Patients with (1) asplenia (right isomerism), (2) polysplenia (left isomerism) and (3) pulmonary/abdominal situs inversus (PASI) plus CHD were included. Terminal TD sidedness was described as left-sided, right-sided, or bilateral. Results: Of 115 eligible patients, the terminal TD was visualized in 56 (49 %). The terminal TD was left-sided in 25 patients, right-sided in 29, and bilateral in two. On univariate analysis, terminal TD sidedness was associated with atrial situs (p = 0.006), abdominal situs (p = 0.042), type of heterotaxy (p = 0.036), the presence of pulmonary obstruction (p = 0.041), superior vena cava sidedness (p = 0.005), and arch sidedness (p < 0.001). On multivariable analysis, only superior vena cava and aortic arch sidedness were independently associated with terminal TD sidedness. Conclusions: Terminal TD sidedness is highly variable in patients with heterotaxy. Superior vena cava and arch sidedness are independently associated with terminal TD sidedness. Type of heterotaxy was not independently associated with terminal TD sidedness. This data improves the understanding of anatomic variation in patients with heterotaxy and may be useful for planning for lymphatic interventions.